2008
DOI: 10.1634/stemcells.2008-0184
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: IFATS Collection: Selenium Induces Improvement of Stem Cell Behaviors in Human Adipose-Tissue Stromal Cells via SAPK/JNK and Stemness Acting Signals

Abstract: In the present study, the potential of selenium to enhance stem cell behavior through improvement of human adipose tissuederived stromal cells (ATSCs) and the associated molecular mechanism was evaluated. Selenium-induced improvement in stem cell behavior of human ATSCs caused expression of several genes, indicating downregulated mature cell marker proteins coupled with increased cell growth and telomerase activities after the overexpression of Rex1, Nanog, OCT4, SOX2, KLF4, and c-Myc. Also, selenium-treated A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 37 publications
3
27
0
Order By: Relevance
“…However, the levels of p38 and p-SaPK/jnK coupled with the inhibition of p53 and p21 tumor suppressor gene products were markedly down-regulated in curcumin-treated 3t3-l1 cells. in particular, reX1 overexpression after curcumin treatment is consistent with our recent reports in which enhancement of reX1 expression causes an increase in the proliferation efficiency of cells (34,35). we next investigated the effects of curcumin on the migration of 3t3-l1 cells in order to show that increased cell proliferation by curcumin was related to the migration efficiency.…”
Section: Discussionsupporting
confidence: 92%
“…However, the levels of p38 and p-SaPK/jnK coupled with the inhibition of p53 and p21 tumor suppressor gene products were markedly down-regulated in curcumin-treated 3t3-l1 cells. in particular, reX1 overexpression after curcumin treatment is consistent with our recent reports in which enhancement of reX1 expression causes an increase in the proliferation efficiency of cells (34,35). we next investigated the effects of curcumin on the migration of 3t3-l1 cells in order to show that increased cell proliferation by curcumin was related to the migration efficiency.…”
Section: Discussionsupporting
confidence: 92%
“…In the DM + T group, injected ADSCs were able to be localized to the bladder. This may be attributable to homing factors such as SDF-1, as ADSCs have been shown to express the SDF-1 receptor CXCR4 and migrate to SDF-1 in cell migration assays [20]. In our previous in vivo study, SDF-1/CXCR4 also appears to mediate migration of ADSCs toward prostate tumor in mice [21].…”
Section: Discussionmentioning
confidence: 91%
“…Expression of these pluripotency factors has since been confirmed in human ASCs [117,[174][175][176], canine ASCs [177], rodents [174], and pig [178]. While a functional role for such factors in ASCs remains unclear, Kim et al have shown that exogenous overexpression of OCT4 results in increased telomerase activity, increased expression of numerous pluripotency markers including Nanog, Sox2, and Klf4 [179], and decreases in other genes associated with differentiation, such as nestin, Smad3, and FOXO1. Earlier studies have proposed that the increased expression of Oct4, Nanog, and Rex-1 upon the treatment of ASCs with selenium results in their reprogramming and produces more "primitive stem cells" capable of enhanced mesodermal differentiation [179].…”
Section: Pluripotency Of Ascs: Es Markersmentioning
confidence: 99%